Effect of Heat Stress During Transport and Rest Before Slaughter, on the Metabolic Profile, Blood Gases and Meat Quality of Quail - Gonzalez, V.A.; Rojas, G.E.; Aguilera, A.E.; Flores-Peinado, S.C.; Lemus-Flores, C.; Olmos-Hernandez, A.; Becerril-Herrera, M.; Cardona-Leija, A.; Alonso-Spilsbury, M.; Ramirez-Necoechea, R.; Mota-Rojas, D. (International Journal of Poultry Science, 2007)
Currently in Mexico there is no regulation ruling over transportation and the rest period before slaughtering quail. An experiment was carried out to evaluate transportation and rest period effects before sacrifice on the metabolic profile, blood gas, pH and meat quality of the Japanese quail carcass. Sixty quail (Coturnix coturnix japonica) were transported to slaughter, on arrival they were randomly divided in 2 groups: with (4 hours) rest and without rest (slaughtered right away). A blood simple was taken before and post sacrifice. After transportation, the rested quail had significantly lower lactate levels (p<0.05), compared to the quail without rest (36.33±6.17 vs. 21.64±2.14, respectively). The results showed that when quail are stressed, pCO2 and lactate levels tend to diminish significantly (p<0.05) compared to mammals. Rest showed a direct effect on temperature (p<0.05), diminishing acidity, reflected though hot and cold carcass pH as compared to the group of quail without rest.